2014
DOI: 10.1371/journal.pone.0098738
|View full text |Cite
|
Sign up to set email alerts
|

Additional Nitrogen Fertilization at Heading Time of Rice Down-Regulates Cellulose Synthesis in Seed Endosperm

Abstract: The balance between carbon and nitrogen is a key determinant of seed storage components, and thus, is of great importance to rice and other seed-based food crops. To clarify the influence of the rhizosphere carbon/nitrogen balance during the maturation stage of several seed components, transcriptome analysis was performed on the seeds from rice plants that were provided additional nitrogen fertilization at heading time. As a result, it was assessed that genes associated with molecular processes such as photosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…5 In this regard, several authors have reported critical differences among cultivars featured by an average protein content, as a consequence of foliar fertilization, upon field trials developed in soils with similar composition. 28 In addition, Bezus et al and Vidal et al evaluated genotypes featured by high protein content and did not observe a statistically significant response to the nitrogen fertilization applied. 30 Additional studies by the same authors evidenced that the response varies according to the genotype, which has been justified because the applied N can be directed to other destinations different from grain, as yield or biomass, for which it is necessary to evaluate higher doses and other moments of application.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…5 In this regard, several authors have reported critical differences among cultivars featured by an average protein content, as a consequence of foliar fertilization, upon field trials developed in soils with similar composition. 28 In addition, Bezus et al and Vidal et al evaluated genotypes featured by high protein content and did not observe a statistically significant response to the nitrogen fertilization applied. 30 Additional studies by the same authors evidenced that the response varies according to the genotype, which has been justified because the applied N can be directed to other destinations different from grain, as yield or biomass, for which it is necessary to evaluate higher doses and other moments of application.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Moderate N rates enhanced starch accumulation in rice, wheat, and normal maize . The high starch content under MN might be attributed to the increased number of cells and starch granules in the endosperm because of the enhanced activities of soluble and bound invertases and sucrose synthase . The activities of adenosine diphosphate‐glucose pyrophosphorylase, starch synthase, starch branching enzyme, and sucrose phosphate synthase involved in starch synthesis were increased under a low N rate in rice .…”
Section: Resultsmentioning
confidence: 99%
“…The activities of adenosine diphosphate‐glucose pyrophosphorylase, starch synthase, starch branching enzyme, and sucrose phosphate synthase involved in starch synthesis were increased under a low N rate in rice . The low starch content observed under a high N rate might be caused by the downregulation of genes related to starch synthesis . Moreover, a sufficient assimilate supply favoring starch accumulation was demonstrated by N fertilizer additions or ear truncation …”
Section: Resultsmentioning
confidence: 99%
“…This reduction in cell wall components is accompanied by reduced stem mechanical strength, increased lodging, and reduced disease resistance [ 68 , 69 , 70 ]. Similar to roots, expression of cellulose and lignin synthesis genes is reduced in filling seeds in response to high N. This leads to reduced accumulation of both cellulose and lignin in seed endosperms [ 71 ]. In line with this observation, N deficiency leads to an increase in cellulose content in the roots of rice plants [ 72 ].…”
Section: Influence Of Nutrient Availability On Cell Wall Compositimentioning
confidence: 99%